Editorial: smoking status and 5‐year survival in patients with colorectal cancer. Issue 8 (21st March 2017) - Ho, N.; Lieberman, D.
Abstract : Linked Content This article is linked to Sharp et al paper. To view this article visithttps://doi.org/10.1111/apt.13944 .